Castel di Sangro-Scontrone field camp – structural and applied geomorphology. Issue 5 (19th October 2016) - Miccadei, Enrico; Piacentini, Tommaso; Antoniani, Federica; Caporali, Lorenza; Carducci, Andrea; Cerone, Davide; Cerritelli, Francesca; D'Amico, Antimo; De Angelis, Chiara; De Filippis, Rino; De Santis, Antonio; Di Matteo, Andrea; et al.
ABSTRACT: The Geomorphological Field Camp 2014 in the Castel di Sangro-Scontrone area is the result of geological and geomorphological teaching field work activities carried out in Central Italy by a group of 23 students attending the Structural Geomorphology and Applied Geomorphology courses (Master's Degree in Geological Science and Technology of the Università degli Studi 'G. d'Annunzio' Chieti-Pescara, Italy, Department of Engineering and Geology). The Field Camp 2014 was organized in May 2014, following regular classes held during the fall term. General activities for the field camp were developed over four main stages: (1) preliminary analysis of the regional geological and geomorphological setting of the area; (2) preliminary activities for the analysis of the local area (orography, hydrography and photogeology investigations, and geographical information system processing); (3) field work, focused on the analysis of a specific issue concerning structural geomorphology or applied geomorphology (e.g. landscape evolution, river channel change, landslide distribution, and flood hazard); and (4) post-field work production of the map. Finally, the fundamental role of field work in the analysis of landscape and in land management was outlined: indeed, the overall field camp enhanced the crucial role of field-based learning for young geomorphologists in order to acquire a strong sensitivity to geomorphological processes and landscape evolution.